Infertility-related stress and marital intimacy among infertile couples undergoing in vitro fertilization treatment in Western Iran: A cross-sectional study - Sara Abdoli; Salman Khazaei; Faezeh Fazli; Shamim Pilehvari; Ensiyeh jenabi (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Background: Given the fundamental role of fertility and childbearing in Iranian families, along with its cultural and social dimensions, and considering the importance of paying attention to marital issues among infertile couples, despite the limited and contradictory studies in this area, the present research aimed to Study marital intimacy and infertility stress in infertile couples undergoing in Vitro Fertilization (IVF) treatment in the west of Iran. Methods: In 2023, a cross-sectional study from 1 September until December was undertaken on 117 couples at an Infertility Center in Hamadan City, Iran. Measurement tools were demographic characteristics, Newton's infertility stress questionnaire and the marital intimacy questionnaire. A convenience sampling method was utilized to recruit a total of 117 eligible women, each part of a couple, for the study. All participants completed the questionnaires of demographic characteristics, newton's infertility stress and the marital intimacy as required. Data analysis was carried out using Stata-17 software, with significance set at a level below 0.05. Results: In the present study the number of 234 cases was investigated. There wasn't a significant difference observed in infertility-related stress domains by gender (P > 0.05).Significant direct correlations were observed between infertility-related stress and age (r = 0.55, P < 0.001), duration of marriage(r = 0.72, P < 0.001), duration of infertility (r = 0.64, P < 0.001), and duration of treatment (r = 0.67, P < 0.001). Conversely, marital intimacy exhibited significant inverse correlations with these variables (P < 0.001). Additionally, a significant negative correlation was found between marital intimacy and infertility-related stress (r = -0.67, P < 0.001). Conclusion: The present study has shown that the mean score of marital intimacy among women is significantly higher than men. Additionally, there is a significant negative correlation between marital intimacy and infertility-related stress. Considering the importance of mental health in infertile couples and its potential impact on the outcome of IVF treatment, it appears that supportive interventions and counseling sessions to increase marital intimacy in infertile couples undergoing IVF treatment.